SMC-Flood database: a high-resolution press database on flood cases for the Spanish Mediterranean coast (1960-2015). - Gil Guirado, Salvador; Pérez-Morales, Alfredo; López-Martínez, Francisco (European Geosciences Union, 2019)
Flood databases of high spatio-temporal resolution are a necessary tool for proper spatial planning, especially in areas with high levels of exposure and danger to floods. This study presents the preliminary results of the Spanish Mediterranean Coastal Flood (SMC-Flood) database covering the municipalities in this region. This database collects information on flood cases that occurred between 1960 and 2015 by systematically consulting the digital archives of the main newspapers in the study area. The search for flood information was conducted by means of using links between municipality names and seven keywords that correspond to the most common ways of referring to a situation that is likely to describe a flood in Spain. This methodology has enabled the reconstruction of 3008 flood cases at a municipal scale with daily resolution while gathering information on the types of damage, intensity, severity and area affected. The spatio-temporal analysis of the data reveals hotspots where flood cases are especially intense and damaging when compared to highly developed areas where the frequency of flood cases is very high. This situation is especially worrying insofar as we have detected a growing trend in the frequency and area affected by flood cases. However, one positive aspect is that the intensity and severity of flood cases follows a falling trend. The main novelty lies in the fact that the high-resolution spatial analysis has made it possible to detect a clear latitudinal gradient of growing intensity and severity in a north–south direction. This pattern calls for new actions by the coastal municipal authorities of southern Spain for adaptation to a more complex flood scenario.
Keywords: Inundaciones - Mediterráneo (Región); Prensa; Inundaciones; Base de datos